DNA Methylation of Patatin-Like Phospholipase Domain-Containing Protein 6 Gene Contributes to the Risk of Intracranial Aneurysm in Males - Zhou, Shengjun; Zhang, Junjun; Zhou, Chenhui; Gong, Fanyong; Zhu, Xueli; Pan, Xingqiang; Sun, Jie; Gao, Xiang; Huang, Yi (Frontiers in Aging Neuroscience, 2022)
Objective: This study aimed to investigate the contribution of patatin-like phospholipase domain-containing protein 6 (PNPLA6) DNA methylation to the risk of intracranial aneurysm (IA) in a Han Chinese population. Methods: A total of 96 age- and sex-matched participants were recruited to evaluate PNPLA6 methylation via bisulfite pyrosequencing. The PNPLA6 mRNA expression in the plasma was determined using real-time quantitative reverse transcription-polymerase chain reaction. Human primary artery smooth muscle cells (HPCASMC) were used for the vitro function study. Results: PNPLA6 methylation was significantly higher in patients with IA than in healthy controls (p < 0.01). Sex group analysis showed that this correlation appeared in the male group (p < 0.01) but not in the female group (p > 0.05). PNPLA6 methylation was significantly associated with age in all participants (r = 0.306, p = 0.003) and in the control group (mean methylation: r = 0.377, p = 0.008) but not in the IA group (r = 0.127, p = 0.402). Furthermore, the PNPLA6 mRNA expression significantly decreased in patients with IA than that in the controls (p = 0.016). PNPLA6 expression was significantly inversely correlated with elevated DNA methylation in participants (r = −0.825, p < 0.0001). In addition, PNPLA6 transcription was significantly enhanced following treatment with 5-aza-2’-deoxycytidine methylation inhibitor in HPCASMC. The receiver operating characteristic analyses of curves showed that the PNPLA6 mean methylation (area under the curve [AUC] = 0.74, p < 0.001) and mRNA expression (AUC = 0.86, p < 0.001) could have a diagnostic value for patients with IA. Conclusion: Although future functional experiments are required to test our hypothesis, our study demonstrated that PNPLA6 methylation and mRNA expression were significantly associated with the risk of IA; thus, they show potential for use in the early diagnosis of IA.